Algorithms of Energy Efficient Control of Electric Technological Complex for Autonomous Heat Supply - Breido, J.V.; Kalinin, A.A.; Lissitsyn, D.V. (EAI Endorsed Transactions on Energy Web, 2018)
The algorithms for energy efficient control of an electric technological complex with a frequency-controlled electric drive for autonomous heat and hot water supply based on hydrodynamic heaters have been developed. The complex is designed to carry out experimental studies of the problem of reducing energy consumption by hydrodynamic heaters. The functional and process flow sheet of the complex is given. The results of experimental studies confirming the effectiveness of the developed algorithms are presented. Power consumption reducing by 8% was achieved owing to the cyclic operation, and up to 45% due to capacity control of the pump unit.